(untitled) (Economics and region, 2019)
It is considered essential features of social obligations of the State in the system connection with constitutional rights and guarantees of citizens. It is also considered the sources and directions for the use of public financial resources, taking into account the particularities of the manifestation of budgetary relations. This paper confirmed the existence of a political component in the actions of the participants of the budgeting process by artificial restrictions on social standards due to the limited financial resources of the State. The authors formed important proposals for actual, rather than declarative socially oriented budget.